2015
DOI: 10.1016/j.bbcan.2014.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cancer metastasis by cell-free miRNAs

Abstract: MicroRNAs (miRNAs) are integral molecules in the regulation of numerous physiological cellular processes that have emerged as critical players in cancer initiation and metastatic progression, both by promoting and suppressing metastasis. Recently, cell-free miRNAs shed from cancer cells into circulation have been reported in cancer patients, raising hope for development of novel biomarkers that can be routinely measured in easily accessible samples. In fact, establishing miRNA expression in the circulation lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 313 publications
(378 reference statements)
2
67
0
Order By: Relevance
“…In fact, several studies have reported the use of circulating miRNAs as biomarkers to predict tumor progression and the presence of bone metastases. [51][52][53][54] Furthermore, highly expressed circulating miRNAs from cancer patients have been reported to return to a normal level after tumor resection, 55,56 suggesting that the level of circulating miRNAs reflects the disease state of the patient to some extent and could be used as a pharmacodynamic marker. Moreover, cell-free and exosomal miRNAs are of particular interest owing to their pleiotropic roles in modulating many physiological and pathological processes, including cancer metastasis.…”
Section: Bone-derived Mirnas In Bone Metastasismentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, several studies have reported the use of circulating miRNAs as biomarkers to predict tumor progression and the presence of bone metastases. [51][52][53][54] Furthermore, highly expressed circulating miRNAs from cancer patients have been reported to return to a normal level after tumor resection, 55,56 suggesting that the level of circulating miRNAs reflects the disease state of the patient to some extent and could be used as a pharmacodynamic marker. Moreover, cell-free and exosomal miRNAs are of particular interest owing to their pleiotropic roles in modulating many physiological and pathological processes, including cancer metastasis.…”
Section: Bone-derived Mirnas In Bone Metastasismentioning
confidence: 99%
“…carriers, such as HDL or LDL, or packaged into microvesicles such as exosomes (30-100 nm) or larger microparticles (100-1000 nm). 51 The presence of their protein-or lipid-based carriers or their encapsulation into vesicles confer circulating miRNAs remarkable stability under a variety of harsh environmental conditions. 50,51 As such, secreted miRNAs represent important potential biomarkers for diagnosis and prognosis that can be detected by noninvasive means in a reliable and reproducible manner.…”
Section: Bone-derived Mirnas In Bone Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes are small membrane vesicles that are known to contain miRNAs, proteins, mRNAs, noncoding RNAs (ncRNA), lipids, proteins, and cellular constituents (Thery et al 2009). Emerging studies have shown that exosomes are essential for cell-to-cell communication throughout the body and play an important role in dissemination of disease (Alečković and Kang 2015), host-pathogen interactions (Schorey et al 2014), and regenerative medicine (De Jong et al 2014). Yang and colleagues (2014) have recently described the detection of tumor cell-specific mRNA in salivary exosome-like microvesicles of a novel human lung cancer xeongraft mouse model.…”
Section: The Neonatal Salivary Transcriptomementioning
confidence: 99%
“…Binding of miRNAs to their target mRNAs along with the RISC complex mediates inhibition of translation initiation (5). miRNA involvement in cancer development and metastasis is the subject of intense research (6)(7)(8)(9)(10).…”
mentioning
confidence: 99%